TRADISI ILMIAH DALAM PERADABAN ISLAM MELAYU - Maryamah Maryamah (Tadrib: Jurnal Pendidikan Agama Islam, 2016)
Growth and development of the scientific tradition in the archipelago go hand in hand with the entry and development of Islam in the archipelago. In this case a lot of theories that spoke of the beginning of the arrival of Islam in the archipelago region. In general, the theories associated with shipping lines and trade relations between the Arab world with East Asia. The island of Sumatra, for example, because of its geographical position, since the beginning of the first century AD has become the foundation of trade between nations and traders who came to Sumatra.Since the initial development of Islam, education top priority Nusantara Muslim community. In addition because of the great importance of education, interests Islamisation encourage Muslims in the teaching of Islam in spite of the simple system, where teaching is given with halaqah system conducted in places of worship some sort of mosques, prayer rooms, and even in the homes of scholars. The need for education to encourage people adopting Islam in the archipelago and transfer of religious and social institutions that already exist in Islamic educational institutions in the archipelago. Muslims in Java transfer Hindu-Buddhist educational institutions into boarding schools, the Muslims took over surau in Minangkabau as a relic of indigenous local communities into Islamic educational institutions, and so are the people of Aceh by transferring public institutions meunasah as Islamic educational institutions.